2012
DOI: 10.1111/j.1349-7006.2012.02367.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferase 5 is a potential oncoprotein that upregulatesG1 cyclins/cyclin‐dependent kinases and the phosphoinositide 3‐kinase/AKTsignaling cascade

Abstract: Increasing evidence suggests that PRMT5, a protein arginine methyltransferase, is involved in tumorigenesis. However, no systematic research has demonstrated the cell‐transforming activity of PRMT5. We investigated the involvement of PRMT5 in tumor formation. First, we showed that PRMT5 was associated with many human cancers, through statistical analysis of microarray data in the NCBI GEO database. Overexpression of ectopic PRMT5 per se or its specific shRNA enhanced or reduced cell growth under conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
153
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(167 citation statements)
references
References 46 publications
9
153
5
Order By: Relevance
“…This change is consistent with the predominant expression of PRMT5L in HeLa cells (Fig. 2C and 4B) and its mitosis-promoting effect (41,(44)(45)(46)61). Importantly, as anticipated, rescue with MycPRMT5L significantly reduced the proportion of interphase cells to 28.7% (Ϯ6.6%, P ϭ 0.002) (Fig.…”
Section: Evolutionary "Invasion" Of G 5-8 Into the Upstream 3=ss Of Asupporting
confidence: 87%
See 3 more Smart Citations
“…This change is consistent with the predominant expression of PRMT5L in HeLa cells (Fig. 2C and 4B) and its mitosis-promoting effect (41,(44)(45)(46)61). Importantly, as anticipated, rescue with MycPRMT5L significantly reduced the proportion of interphase cells to 28.7% (Ϯ6.6%, P ϭ 0.002) (Fig.…”
Section: Evolutionary "Invasion" Of G 5-8 Into the Upstream 3=ss Of Asupporting
confidence: 87%
“…Consistent with the known function of PRMT5 in promoting cell proliferation (41,(44)(45)(46)61), PRMT5L-preferred genes were significantly enriched in functional clusters of cell growth and proliferation. Strikingly, the functions of the 50 PRMT5S-preferred genes clustered most significantly in cell death and cell cycle arrest pathways (Fig.…”
Section: Evolutionary "Invasion" Of G 5-8 Into the Upstream 3=ss Of Asupporting
confidence: 65%
See 2 more Smart Citations
“…14 Increased proliferation, induced anchorage-independent colony growth, as well as tumorigenesis were found when PRMT5 is overexpressed; therefore, PRMT5 has been considered a promising target for cancer therapy. [15][16][17] Recently, several studies indicated that PRMT5 plays important roles in breast tumorigenesis. [18][19][20][21] It is reported that PRMT5 binds to the zinc finger structures in tumor necrosis factor receptor-associated factor 4 (TRAF4) and is regulated by this scaffold protein; TRAF4 participates in nuclear factor (NF)-κB signaling and is involved in the promotion of cell proliferation and survival in breast cancer.…”
Section: Introductionmentioning
confidence: 99%